APPLYING CLUSTERING TECHNIQUE TO IMPROVE CREATIVE WRITING SKILLS FOR JUNIOR HIGH SCHOOL STUDENTS IN DESCRIPTIVE TEXT - Husda, Azizah; Lubis, Bambang Nur Alamsyah; Yunanda, Fachri; Asrul, Nurmahyuni (English Language Teaching Prima Journal (ELT), 2023)
This study explores the application of the clustering technique to enhance creative writing on the descriptive text for junior high school students at SMP Marisi Medan. The research question focuses on assessing the effectiveness of the clustering technique in writing descriptive text. The objective is to determine whether the use of the clustering technique significantly affect to enhance students' writing skills. The research adopts a pre-experimental design, within the population of 298 eighth-grade students. The sample consists of 20 students, selected through purposive sampling. The research employs a writing test comprising both pre-test and post-test assessments. Following the application of the clustering technique in teaching descriptive writing, the post-test mean score (79.0) surpasses the pre-test mean score (64.0). The hypothesis testing results, with a Sig. (2-tailed) score of 0.000 less than 0.05, lead to the rejection of H0 and acceptance of H1. In essence, the findings indicate a significant positive impact of utilizing the clustering technique on the effectiveness of students' descriptive writing skills.